STUDI PERBANDINGAN KURIKULUM PENDIDIKAN SAINS INDONESIA DENGAN AUSTRALIA - Barkah, Eka; Jovianto, Andrean; Muktiningsi, Muktiningsi; Ridwan, Achmad (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Science education has an important role in preparing young people with relevant knowledge and skills to face global challenges in the 21st century. In its implementation, Indonesia and Australia have several similarities and differences in aspects of its implementation. This article explores the comparison between science curricula in Indonesia and Australia, focusing on structure, approaches, and learning objectives. Indonesia's Kurikulum Merdeka is designed to integrate local values such as Pancasila through project-based approaches, while the Australian Curriculum prioritizes inquiry-based learning with a focus on global innovation and sustainability. This study employs a qualitative literature review method to identify the similarities and differences between the two curricula. Similarities include an emphasis on scientific literacy, the integration of technology in learning, and contextual approaches linking content to real-life applications. Significant differences lie in curriculum structure, implementation flexibility, and periodic updates. The study highlights that both curricula possess unique strengths that can complement each other to improve the quality of science education at global level. This article offers valuable insights for educators and policymakers in developing adaptive and relevant curricula for modern challenges.